Trajectories of the Discourse on Transnational Organized Crime : Biopolitical Wars and Global Civil Society Conceptualizing Transnational Organized Crime (2001)
The article aims to understand how the dominant conceptualization of transnational crime legitimates non-traditional forms of warfare at the global level while itself constituting the idea of global civil society. It is argued that since this discourse defines transnational crime as a threat to global society, it makes politically viable the deployment of policing and military interventions in defence of the world population. In order to expose this, this article reconstructs the trajectories of the discourse on organized criminality. The article first analyses the emergence of the discourse in the United States during the 1950s, afterwards analysing it as an issue of transnational scope during the last two decades. Thus the aim here is to underline the importance that a phenomenon such as crime has had on the governance at a global level.